Evaluating active travel : decision-making for sustainable city - Macmillen, J; Givoni, M; Banister, D (Alexandrine Press, 2010)
It is now widely recognized that active travel the collective term for walking and cycling confers a multitude of individual and societal benefits that are qualitatively different from those generated by motorized transport. Regular pedestrians and cyclists can expect to enjoy potential health benefits, while modal shift to active travel can lead to considerable environmental improvements at a broad range of spatial scales. However, given the need to ensure high-quality decision-making in the transport sector, it is paramount that contemporary evaluation practices keep pace with the shifting nature of policies that explicitly encourage uptake of walking and cycling. Drawing on a numerical example, this paper examines the extent to which the United Kingdom Department for Transport's evaluation framework NATA is sufficiently capable of determining the likely value of investments in active travel and hence whether there is confidence that policy-makers are adequately placed to make informed choices between alternative investments. It is argued that while the overarching logic to evaluating active travel remains relatively sound, changes must be made to the framework if a genuine transition to sustainable urban mobility is to occur.